Social support as a mediator between life events and non-suicidal self-injury: evidence for urban-rural moderation in medical students - Lin, Zhumei; Zhang, Yiwen; Kong, Siru; Ruan, Qianan; Zhu, Li-Li; Li, Cheng-Han (Frontiers in Psychiatry, 2025)
BackgroundNon-suicidal self-injury (NSSI) among medical students represents a critical public health concern, yet the protective mechanisms and their effectiveness across different demographic contexts remain poorly understood. This study investigates how social support mediates the relationship between negative life events and NSSI, while examining the moderating effect of urban-rural origins.MethodsA cluster sampling approach was employed to survey 1,130 first-year medical students (471 males, 659 females; mean age 18.15 ± 0.63 years; response rate: 98.5%) at Xiamen Medical College, including 473 urban and 657 rural students. Participants completed the Adolescent Self-Rating Life Events Checklist, Social Support Rating Scale, and Adolescent Self-Injury Questionnaire. Harman’s single-factor test confirmed no significant common method bias. Hayes’ PROCESS macro (Model 7) was used to test the moderated mediation model, with bootstrapping (5,000 resamples) for significance testing.ResultsCorrelation analysis revealed significant associations between life events and NSSI (r = 0.28, p <.01), life events and social support (r = -0.36, p <.01), and social support and NSSI (r = -0.19, p <.01). The mediation analysis showed that social support partially mediated the relationship between negative life events and NSSI (indirect effect = 0.01, 95% CI [0.002, 0.016]), accounting for 14.7% of the total effect. Life events significantly predicted social support (β = 0.56, p <.001) and NSSI (β = -0.02, p <.001). The moderation analysis revealed that birthplace significantly moderated the relationship between life events and social support (β = 0.16, p <.05), with urban students showing greater vulnerability to reduced social support (β = -0.14, p <.001) compared to rural students (β = -0.10, p <.05).ConclusionsThis study reveals that while social support serves as a crucial buffer against NSSI, its protective effect varies significantly between urban and rural students. Contrary to traditional resource-based assumptions, urban students demonstrated greater vulnerability to stress-induced reduction in social support. These findings suggest the need for targeted interventions that consider students’ geographical backgrounds when developing support systems in medical education.